Wisdom and Mystical Thoughts on The Mirror-Tiles Art in Safavid Architectural Space and its Relationship With Sufism - Naeim Sepehri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
The Mirror-tiles artwork is one of the latest initiatives of Iranian spiritual art which with its symbolic expression and mysterious character, conveys the revelations and mystical thoughts in the cover of matter and form to its audience and affects them consciously and unconsciously. This art is an esoteric language to convey intuitive concepts and to remind the way of their inherited life from the predecessors as traditional art has always been based on symbols and allegories and expresses the spirit of its time. The first peak of the Mirror-tiles used in architectural spaces in Iran coincided with the fusion of Sufism and Shi’ism in the early period of the Safavid Empire. The Safavid dynasty had Sufi roots and lineage, and among the Sufis, the inner language is the language of Shari’a and Truth, and the tools of that language are the symbol and indication. Has been rejected or neglected due to a lack of interest and attention to the registration of special documents, the secrets governing this system, new historical conditions, and profound and obvious developments in the realm of contemporary history. With the aim of the influence of the Persian mystical thoughts about the Mirror, this study with the available historical and contemporary sources and analyzing them deals with the hidden meanings in this art and reveals its connection with Sufism and Mysticism through mystical literature and its historical process.